Anticounterfeit packaging technologies - Ruchir Y Shah; Prajesh N Prajapati; Y K Agrawal (Wolters Kluwer Medknow Publications, 2010)
Packaging is the coordinated system that encloses and protects the dosage form. Counterfeit drugs are the major cause of morbidity, mortality, and failure of public interest in the healthcare system. High price and well-known brands make the pharma market most vulnerable, which accounts for top priority cardiovascular, obesity, and antihyperlipidemic drugs and drugs like sildenafil. Packaging includes overt and covert technologies like barcodes, holograms, sealing tapes, and radio frequency identification devices to preserve the integrity of the pharmaceutical product. But till date all the available techniques are synthetic and although provide considerable protection against counterfeiting, have certain limitations which can be overcome by the application of natural approaches and utilization of the principles of nanotechnology.